Resolusi Jihad di Indonesia Perspektif Ketatanegaraan dalam Al- Qur’an - Makinudin, Makinudin (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
Abstract: This article discusses Resolusi Jihad issued by KH Hasyim Asy’ari in 1945 from the perspective of tafsir (Quran interpretation). Among the verses that order to establish Islamic state and defend it are QS. 24: 55; 8: 60; 2: 190-191); 22: 39-40. These verses become justifications to oust colonial power from Indonesia which resulted in proclamation of independence on 17th of August 1945. The returning Dutch were resisted. KH. Hasyim Asy’ari issued a fatwa on 17th of September 1095 that defending newly proclaimed independent Indonesia is a religious duty and considered as jihad (holy war) after the question was posed by Soekarno, the president. This fatwa then was reinforced as Resolusi Jihad on 22nd of October 1945. The Quran does not explain clearly about the necessity to establish an Islamic state. Instead, it only stipulates principles of governance so that the maxim of mâ lâ yatim al-wâjib illâ bih fa huwa wâjib or al-amr bi al-syay’ amr bi wasâilihi is employed. (2) the Quran order muslims to oust and resist colonial power because this colonial power had done injustice, exploitation, and crimes against indigenous muslim population. 3). Resolusi Jihad is an inevitability for a free nation to defend freedom. It has become religiously obligatory to defend nation as it is stipulated in the Quran, especially QS. 2: 190-191 and 8: 60. Key words: Jihad, Resolusi Jihad, tafsir al-Qur’an